2006
DOI: 10.1182/blood-2005-05-2185
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cutaneous lymphocyte-associated antigen as sialyl 6-sulfo Lewis X, a selectin ligand expressed on a subset of skin-homing helper memory T cells

Abstract: We previously identified the carbohydrate determinant sialyl 6-sulfo Lewis X (Le x ) as the major L-selectin ligand on high endothelial venules of peripheral lymph nodes. In this study, we examined the distribution of the sialyl 6-sulfo Le x determinant among peripheral lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 49 publications
2
49
1
Order By: Relevance
“…The binding between sLe x and selectins has been known to be important for regulation of leukocyte migration into inflamed tissues [28 -30]. Recently, it had been reported that the CLA, recognized by the HECA-452 antibody against sialyl 6-sulfo Lewis x antigen, was expressed on a subset of memory CD4 ϩ T cells [18]. In addition, it has been indicated that the HECA-452-defining CLA, binding with E-, P-, and L-selectins, was closely related with skin homing of memory Th cells [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding between sLe x and selectins has been known to be important for regulation of leukocyte migration into inflamed tissues [28 -30]. Recently, it had been reported that the CLA, recognized by the HECA-452 antibody against sialyl 6-sulfo Lewis x antigen, was expressed on a subset of memory CD4 ϩ T cells [18]. In addition, it has been indicated that the HECA-452-defining CLA, binding with E-, P-, and L-selectins, was closely related with skin homing of memory Th cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important oligosaccharides is a fucose-containing tetrasaccharide, serving sialyl Lewis x (sLe x ) as a ligand for the adhesion molecules such as E-selectin and P-selectin on endothelial cells [16,17]. It had been reported that the cutaneous lymphocyte-associated antigen (CLA), recognized by HECA-452 antibody against sialyl 6-sulfo Lewis x antigen, was expressed on a subset of memory CD4 ϩ T cells [18]. In addition, it has been revealed that the HECA-452 defining CLA, binding with E-, P-, and L-selectins, was closely related with skin homing of memory Th cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sialyl Lewis X determinant, the specific carbohydrate ligand for selectins, is constitutively expressed on granulocytes and monocytes and mediates inflammatory extravasation of these cells (4)(5)(6). Most resting peripheral T and B lymphocytes, on the other hand, lack its expression, and are induced to strongly express sialyl Lewis X upon activation (7,8). Among T lymphocytes, the sialyl Lewis X determinant is known to be preferentially expressed on activated Th1 cells but not on Th2 cells (9).…”
mentioning
confidence: 99%
“…The induction of sialyl Lewis X on lymphocytes accompanies transcriptional activation of fucosyltransferase VII gene (FUT7), which is involved in the last step of sialyl Lewis X synthesis (8,(10)(11)(12)(13)(14)(15). Previously, we have shown that the human FUT7 promoter is equipped with binding sites for the cAMP response element (CRE)-binding protein (CREB)͞activating transcription factor (ATF) family, myeloid zinc finger protein 1 (MZF-1) and Sp1 (16,17), and also GATA and T-bet (3).…”
mentioning
confidence: 99%
“…Human T cells express cutaneous lymphocyte Ag (CLA), a ligand for E-selectin (15), and they upregulate CLA after activation in vitro (16,17). In skin biopsies of patients with atopic dermatitis and psoriasis, 80-90% of CD4 and CD8 T cells express CLA (10,18).…”
mentioning
confidence: 99%